Pencegahan Penyakit Lisan Melalui Layanan Informasi Berbasis Hadits (Studi Kualitatif Pada Mahasiswa) - Zhila Jannati (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2020)
Oral is very important to be maintained so that oral disease does not occur. The purpose of this study was to find out how to prevent oral disease through hadith-based information services for Islamic Guidance and Counseling students at UIN Raden Fatah Palembang. This research is a qualitative research. The subjects of this study were 30 students from the Islamic Guidance and Counseling Study Program. The data collection techniques in this study were using observation and interview techniques. The result of this study is that the implementation of hadith-based information services in preventing oral disease is carried out through five stages, namely planning, organizing service elements and targets, implementation, assessment, and follow-up and reports. Thus, it can be concluded that hadith-based information services can be an alternative in preventing oral diseases in students from the Islamic Guidance and Counseling Study Program.